2015
DOI: 10.1002/rcm.7248
|View full text |Cite
|
Sign up to set email alerts
|

Ghost peaks observed after atmospheric pressure matrix-assisted laser desorption/ionization experiments may disclose new ionization mechanism of matrix-assisted hypersonic velocity impact ionization

Abstract: RATIONALE Understanding the mechanisms of MALDI promises improvements in the sensitivity and specificity of many established applications in the field of mass spectrometry. This paper reports a serendipitous observation of a significant ion yield in a post-ionization experiment conducted after the sample has been removed from a standard atmospheric pressure (AP)-MALDI source. This post-ionization is interpreted in terms of collisions of microparticles moving with a hypersonic velocity into a solid surface. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…These authors demonstrated that the most efficient ionization was obtained from a surface with lower melting point, accessible K + ion, and rough texture. Moskovets proposed an explanation for the ionization of residual peptides in the inlet of the mass spectrometer after atmospheric pressure MALDI experiments . A linear ion trap with a three-stage high pressure ion funnel was used to detect the peptides without laser irradiation.…”
Section: Traditional Ionization Methods For Msmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors demonstrated that the most efficient ionization was obtained from a surface with lower melting point, accessible K + ion, and rough texture. Moskovets proposed an explanation for the ionization of residual peptides in the inlet of the mass spectrometer after atmospheric pressure MALDI experiments . A linear ion trap with a three-stage high pressure ion funnel was used to detect the peptides without laser irradiation.…”
Section: Traditional Ionization Methods For Msmentioning
confidence: 99%
“…Moskovets proposed an explanation for the ionization of residual peptides in the inlet of the mass spectrometer after atmospheric pressure MALDI experiments. 147 A linear ion trap with a three-stage high pressure ion funnel was used to detect the peptides without laser irradiation. The ions appeared with decreased background pressure in the first funnel, which may indicate matrix-assisted hypersonic-velocity impact ionization of the peptides.…”
Section: ■ Traditional Ionization Methods For Msmentioning
confidence: 99%